Determinants of Child Growth in Palestine (Ages 5–17): A Structural Equation Modeling Approach to Food Insecurity, Nutrition, and Socioeconomic Factors - Suleiman Thwib; Radwan Qasrawi; Ghada Issa; Malak Amro; Razan Abu Ghoush; Sabri Saghir; Doa’a Mujahed; Maysaa Nemer; Mousa Halaika; Manal Badrasawi; Ayoub Al-Jawaldeh; Ibrahim Elmadfa; et al. (Children)
Background: The growth patterns of children and adolescents are influenced by multiple factors. This study employed structural equation modeling (SEM) to determine the primary factors influencing the growth of Palestinian children and adolescents in the West Bank (WB). Methods: A cross-sectional survey conducted in 2022 in the WB collected data from 1400 households, of which 500 with children aged 5–17 years and were selected for analysis. The survey assessed household food insecurity, socioeconomic status (SES), parental health history, nutritional awareness, food consumption patterns, and nutrient intake. The latent construct “Child Growth” was measured using Body Mass Index-for-age Z-score (BAZ), height-for-age Z-score (HAZ), and Mean Adequacy Ratio (MAR). SEM was employed to examine the interrelations among latent variables and their observed indicators. Results: Mineral intake showed the strongest direct effect on child growth (β = 0.812, p < 0.001), followed by food availability (β = 0.492), vitamin intake (β = 0.481), SES (β = 0.439), and macronutrient intake (β = 0.383). MAR exhibited the highest factor loading as a growth indicator, while HAZ had limited significance, suggesting its chronic nature. SES influenced growth both directly and indirectly through its effects on food availability and dietary intake pathways. Strong correlations between nutritional knowledge and nutrient classes reflect the interrelationship between behavioral and biological determinants. Conclusions: Both structural and immediate nutritional factors influence child growth. In Palestinian youth, mineral intake, food security, and SES have the greatest influence. These findings offer a framework for understanding the growth determinants of Palestinian youth in the WB and support the development of targeted interventions to improve dietary quality and overall nutritional status.